Extensive Sequence Divergence among Bovine Respiratory Syncytial Viruses Isolated during Recurrent Outbreaks in Closed Herds - Larsen, L. E. (American Society for Microbiology, 2000)
The nucleotides coding for the extracellular part of the G glycoprotein and the full SH protein of bovine respiratory syncytial virus (BRSV) were sequenced from viruses isolated from numerous outbreaks of BRSV infection. The isolates included viruses isolated from the same herd (closed dairy farms and veal calf production units) in different years and from all confirmed outbreaks in Denmark within a short period. The results showed that identical viruses were isolated within a herd during outbreaks and that viruses from recurrent infections varied by up to 11% in sequence even in closed herds. It is possible that a quasispecies variant swarm of BRSV persisted in some of the calves in each herd and that a new and different highly fit virus type (master and consensus sequence) became dominant and spread from a single animal in connection with each new outbreak. Based on the high level of diversity, however, the most likely explanation was that BRSV was (re)introduced into the herd prior to each new outbreak. These findings are highly relevant for the understanding of the transmission patterns of BRSV among calves and human respiratory syncytial virus among humans.